2021
DOI: 10.2478/ausp-2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Developing Adult Learners’ Language Competence in Culture-Based Blended-Learning Course

Abstract: During the last two decades, due to technological possibilities and the spread of the Internet, new forms of learning have originated as an alternative to traditional face-to-face learning – e-learning, online learning, hybrid learning, blended learning, ubiquitous learning, etc. They have become even more popular due to the COVID-19 pandemic as the only solution to implement learning at universities and adult education institutions. This paper will focus on a blended-learning language course designed for adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It has to be added that a course trial was conducted, as suggested in the course framework, among 227 learners from these six countries in 2019, where the face-to-face stage was implemented in class. The results obtained indicate a higher skills' development and greater student satisfaction (Luka, 2021a(Luka, , 2021b, thus emphasizing the necessity of live interaction.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It has to be added that a course trial was conducted, as suggested in the course framework, among 227 learners from these six countries in 2019, where the face-to-face stage was implemented in class. The results obtained indicate a higher skills' development and greater student satisfaction (Luka, 2021a(Luka, , 2021b, thus emphasizing the necessity of live interaction.…”
Section: Discussionmentioning
confidence: 81%
“…Luka, 2019a) and delivered to adult learners in six countries (cf. Luka, 2019bLuka, , 2021a2021b). During the second stage, a culture-based BL multilingual course in ten languages was created and delivered to target groups of adult learners from March 2020 to January 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies were from China (Wang & Huang, 2020;Chen, 2021;Sun & Asmawi, 2023;Meng, 2023), two studies were from the Philippines (Ebron & Mabuan, 2021;Hajan & Padagas, 2021) and one study was from South Korea So & Lee (2013); Thailand Dawilai et al (2017), Japan Dawilai et al ( 2021), Malaysia Leduning & Wah (2013), the United States (Geithner & Pollastro, 2015), Canada (Stouck, 2019), Saudi Arabia Chatta & Haque (2020) and the United Kingdom (Russo et al, 2022). A further study focused on curriculum implementation in six European Union countries -Croatia, Latvia, Slovenia, Romania, Poland and the Czech Republic (Luka, 2021). Four studies used quantitative research designs (Dawilai et al, 2017;Stouck, 2019;Dawilai et al, 2021;Meng, 2023] and one study used a qualitative research design (Ebron & Mabuan, 2021).…”
Section: Study Characteristicsmentioning
confidence: 99%